ANALISIS SWOT UNTUK PEMASARAN DI TOKO BANGUNAN â€œBIMA JAYAâ€ - Cahyo, Bayu Dwi; Sari, Maheni Ika; Hermawan, Haris (Growth, 2023)
Marketing strategy has an important role to achieve business success. In determining the appropriate marketing strategy for the company, analysis is needed to see market needs. This is done by analyzing the business environment, both internal and external, usually called a SWOT analysis. The SWOT analysis is thorough on the strengths, weaknesses, opportunities and threats. This analysis is needed to determine several strategies that exist in the company. One of them is the Bima Jaya Bondowoso Building Shop. This study aims to determine the development of the right strategy based on SWOT analysis to be applied to the Bima Jaya Bondowoso Building Shop. The sampling technique used non-probability sampling by using snow ball sampling. From the results of this study that the results of the Internal and External Matrix have a Stability strategy to develop in the future the strategies that can be applied consist of defensive and offensive strategies, defending and product development. The SWOT matrix analysis is S-O where this strategy takes advantage of the company's strengths to seize opportunities that exist in the external environment. The result of the company's alternative strategy is to develop a marketing strategy that has not been done at the Bima Jaya store before and will be developed by the Bima Jaya store in the future.